2016
DOI: 10.2337/dc16-0094
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Food Reward Activity in Patients With Type 2 Diabetes With Improved Glycemic Control After Bariatric Surgery

Abstract: OBJECTIVEObesity and type 2 diabetes mellitus (T2DM) are associated with altered foodrelated neuronal functions. Besides weight loss, substantial improvement of glucose metabolism in patients with T2DM can be achieved by bariatric surgery. We aimed to target the neuronal and behavioral correlates of improved glycemic control after bariatric surgery. RESEARCH DESIGN AND METHODSTwo patient groups with T2DM were recruited. The treatment group (n = 12) consisted of patients who had undergone Roux-en-Y gastric bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 51 publications
4
42
0
1
Order By: Relevance
“…However, precuneus resting-state activity had been also found to decrease after non-surgical weight-loss 27 , suggesting that weight-loss in general, rather than bariatric surgery itself, might be responsible for such changes. Still, the surgical intervention might lead to more pronounced connectivity modifications after weight reduction following RYGB intervention, compared with non-surgical weight reduction 3 . The reduction in connectivity with the anterior fusiform gyrus might also be due to the massive weight loss induced by surgery, as functional connectivity of the anterior fusiform gyrus has been found to be positively associated with weight status 28 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, precuneus resting-state activity had been also found to decrease after non-surgical weight-loss 27 , suggesting that weight-loss in general, rather than bariatric surgery itself, might be responsible for such changes. Still, the surgical intervention might lead to more pronounced connectivity modifications after weight reduction following RYGB intervention, compared with non-surgical weight reduction 3 . The reduction in connectivity with the anterior fusiform gyrus might also be due to the massive weight loss induced by surgery, as functional connectivity of the anterior fusiform gyrus has been found to be positively associated with weight status 28 .…”
Section: Discussionmentioning
confidence: 98%
“…fMRI can be performed with a block-design, when the participant has to perform a task or is passively exposed to a stimulus, or during resting-state, when the participant is simply laying still in the MRI scanner and is instructed not to focus his/her thoughts on anything specific. Most of the studies that have been performed on patients undergoing bariatric surgery have used a block-design to compare operated patients with lean controls, showing changes in reward-related circuitry activity 3, 4 . Others have used a cross-sectional design, comparing obese patients with a different group of operated patients 5 .…”
Section: Introductionmentioning
confidence: 99%
“…An important brain area that was found in our study in chapter 6 (neural responses to food cues) is the precuneus, a brain area previously implicated in decreased liking of high-energy foods after RYGB (Ochner et al, 2012b). In a previous study that compared neural responses to food cues in RYGB patients at least six months after surgery with neural responses in an obese population not undergoing surgery, precuneus activation was found to be higher in the nonsurgical group (Frank et al, 2016). In addition, resting state activity in the precuneus has been shown to be greater in obese versus lean individuals (Zhang et al, 2015), and to be negatively correlated with obesity preventive eating tendency (Nakamura and Ikuta, 2017).…”
Section: Mechanisms Behind Changed Food Preferences After Rygb-inducesupporting
confidence: 60%
“…Consistent with a central satiating effect of GLP‐1, van Bloemendaal et al reported a decreased preference for food pictures in the insula, amygdala, putamen, and orbitofrontal cortex following short‐term administration of a GLP‐1RA in obese individuals. After Roux‐en‐Y gastric bypass (RYGB), obese T2DM subjects show increased activation in the fusiform gyrus, somatosensory cortex, and frontal middle gyrus along with a marked increase in plasma GLP‐1 level . Although some of these studies have employed visual images as food cues, most have focused on brain areas (gustation, reward, and executive functions), which respond differentially to food versus nonfood stimuli, and no study has examined the modulation of the early sensory response to visual images (irrespective of their food/nonfood content) in cortical visual areas.…”
Section: Introductionmentioning
confidence: 99%
“…After Roux-en-Y gastric bypass (RYGB), obese T2DM subjects show increased activation in the fusiform gyrus, somatosensory cortex, and frontal middle gyrus along with a marked increase in plasma GLP-1 level. 18,19 Although some of these studies have employed visual images as food cues, most have focused on brain areas (gustation, reward, and executive functions), which respond differentially to food versus nonfood stimuli, [20][21][22] and no study has examined the modulation of the early sensory response to visual images (irrespective of their food/nonfood content) in cortical visual areas.…”
mentioning
confidence: 99%